The enigma of cancer polyploidy as deciphered by evolutionary cancer cell biology (ECCB) - Vladimir F. Niculescu; Eugenia R. Niculescu (Academia Medicine)
Evolutionary cancer cell biology reveals that the majority of cancer hallmarks trace their origins back to the premetazoic era. These cancer stem cell hallmarks share deep homology with the oxygen-sensitive non-gametogenic (NG) Urgermline, which evolved from the common ancestor of amoebozoan, metazoan, and fungi (AMF). The genes, gene modules, and gene regulatory networks (GRNs) of the premetazoic cell system are preserved in the ancestral genome compartment of metazoans and humans. The Urgermline serves as a blueprint for all germ and stem cell lineages, including parasitic amoebae. As observed in amoebae, DNA double-strand breaks (DSBs) manifest in the homologous recombination (HR) genes of NG germlines and stem cell lineages when exposed to specific hyperoxic conditions, referred to as AMF hyperoxia, characterized by an oxygen content exceeding 6.0%. The cells lose their stemness and differentiation potential but persist in proliferation as low-grade polyploids (4n) through defective symmetric cell division (DSCD). Genomic integrity can be restored through homotypic cell and nuclear fusion, resulting in the formation of high-grade polyploids known as multinucleated genome repair syncytia, or by inductive hyperpolyploidization of more than 64n, as observed in single-celled polyploid giant cancer cells. Interestingly, low-, middle-, and high-grade polyploidization are not exclusive to cancer and protists. Therefore, we investigate (i) functional polyploidies of healthy cells, including humans, mammals, and protists; (ii) dysfunctional polyploidies of cells with impaired HR and irreparable DNA-DSB defects; and (iii) the restoration of genome integrity through cyst-like and high-grade polyploidization events. Additionally, we explore dysfunction in aging stem cells, hepatocytes, and cardiomyocytes.